Trade-offs between the recovery, exergy demand and economy in the recycling of multiple resources; Resources, Conservation and Recycling; Vol. 167 - Gai L. Limei; Varbanov P. S. Petar Sabev; Fan Yee Van; Klemesh Zh. Zhiri; Romanenko S. V. Sergey Vladimirovich (2021, 2021)
Title screen